A Novel Hybrid Cryptographic Approach for Secure Communication - Arora, Gifty; Hirolikar, Deepali S.; Deore, Shailesh Shivaji; Bajaj, K. K.; Gupta, Praveen Kumar; Jaleel, Uruj; R., Vidya (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This paper introduces a novel hybrid cryptographic system designed to enhance the security and integrity of Device-to-Device (D2D) communication in wireless networks. The system combines Huffman coding and binary encryption to secure data transmission over open public channels. Huffman coding provides efficient block encryption, while binary encryption offers robust key management. The proposed algorithm is tested using Java programming, demonstrating its efficiency in maintaining the integrity of various data types with zero Root Mean Square Error (RMSE) in decryption. The research highlights the importance of secure communication in the modern digital age and offers a solution that addresses the key drawbacks of current communication methods, such as complex network design and high power requirements.